Frequency of Mismatch Repair Protein (MMRP) Deficiency among Young Jordanians Diagnosed with Colorectal Carcinoma (CRC) - Bayan Maraqa; Ghassan Al-Shbool; Osama Abu-Shawer; Mamoun Souleiman; Osama Alshakhatreh; Amal Al-Omari; Hadeel Abdelkhaleq; Ayat Taqash; Maysa Al-Hussaini (Gastroenterology Research and Practice)
Purpose. Microsatellite instability (MSI) caused by mismatch repair protein (MMRP) deficiency is detected in 15% of sporadic colorectal cancers (CRCs). Our aim is to investigate the frequency of MMRP deficiency in young CRC patients, using immunohistochemical analysis. Methods. This study targeted cases of CRC at King Hussein Cancer Center from 2004 until 2012 in patients 45 years of age or younger at the time of diagnosis. Clinicopathological data was obtained from 155 patients’ records. Immunohistochemistry for MLH1, MSH2, PMS2, and MSH6 proteins was performed on paraffin-embedded tissue containing carcinoma. Results. The median age of patient at diagnosis was 38 years. A total of 29 (19%) cases showed deficient MMRP(dMMRP)expression. Loss of expression of PMS2 was seen in 17 cases, 12 cases of which showed loss of MLH1 expression. Loss of expression of MSH6 was seen in 10 cases, 9 of which showed loss of MSH2 expression. One case (3.4%) showed loss of all four MMR proteins, and another case (3.4%) showed loss of PMS2/MLH1 and MSH6. There was a significant association between abnormal MMR protein expression and tumor location proximal to splenic flexure (p value 0.000), pathologic features suggestive of microsatellite instability (p value 0.000), P53 negativity (p value 0.000), and stage (p value 0.02). Patients with dMMRP CRC appeared to have a significantly better overall survival compared to patients with proficient MMRP(pMMRP)(p value 0.02). Loss of MSH2/MSH6 was significantly associated with positive family history of cancer (p value = 0.020). Conclusions. The prevalence of dMMRP tumors in this age group appears to be similar to international literature. dMMRP tumors tends to be associated with earlier stages and better outcomes compared to pMMRP cases. dMMRP can serve as a biomarker for better prognosis. These results are of value in directing the clinical management of young patients with CRC.